Etlingera elatior-mediated green synthesis titanium dioxide nanoparticles and its cytotoxicity - Norman, Ashreen; Abdellatief, Mahmoud; Ghourani, Ala’ Al; Cordova, Kyle E.; Borikul, Nidchakan; Fang, Teh Huey; Che Abdullah, Che Azurahanim (John Wiley and Sons, 2025)
This work looks at the ecologically friendly synthesis of titanium dioxide nanoparticles (TiO2NPs) using Etlingera elatior (EE) and how various calcination temperatures affect their structure. X-ray diffraction (XRD) analysis indicate that the green TiO2NPs' crystallite diameters range from 140.12 to 143.46 nm. Due to the limits of conventional XRD, the green TiO2NPs are further characterised using synchrotron XRD (SXRD). SXRD analysis reveals that when calcination temperatures rise, crystallite size gradually increases, and rutile phase formation occurs. Hydrodynamic processes cause bigger particle sizes in dynamic light scattering (DLS). The absorbance spectra of green TiO2NPs are found to be between 205 and 208 nm. Fourier transform infrared (FTIR) spectroscopy validate the chemical structures of the TiO2NPs present. The Raman analysis confirm the existence of both anatase and rutile phases, which are visible in SXRD. Thermogravimetric analysis (TGA) reveals that owing to high calcination temperatures, thermal degradation is minimal due to organic component loss during the calcination process. Further examination into its environmental toxicity demonstrated that green TiO2NPs are less harmful than commercialised P25 titania in a brine shrimp lethality assay. The study's findings show that green synthesis is environmentally safe. Aside from that, calcination for green TiO2NPs is unnecessary in future work as it increases particle size as shown in SXRD.